Mediating Effect of Cognitive Function on the Relationship Between Geriatric Oral Health and Quality of Life Among Korean Seniors - Eun Jee Chang; Hyun-Jae Woo; Kyu-Hyoung Jeong (Korean Society for Preventive Medicine, 2022)
Objectives Previous studies have found that the oral health of seniors can affect their physical nutrition and quality of life (QoL). Additionally, poor oral health can lead to the development of dementia, which is associated with decreased cognitive function. This study aimed to examine the impact of geriatric oral health (GOH) on the QoL of Korean seniors and the mediating effects of cognitive function. Methods We used data from the seventh Korean Longitudinal Study of Aging conducted in 2018. In total, 4049 seniors were included in our study. We analyzed the impact of GOH on QoL according to 5 mediating domains of cognitive function and control variables. To examine each path of mediating effects, bootstrapping with 5000 iterations was performed with 95% confidence intervals. Results Our findings revealed that good GOH had a positive effect on the QoL of seniors. Also, better GOH corresponded to a higher degree of cognitive function within all 5 domains: orientation, memory registration, attention/calculation, memory recall, and language and visuospatial ability. In addition, 3 domains of the 5 domains (attention/calculation, memory recall, and language and visuospatial ability) had significant mediating effects on the relationship between GOH and QoL. Conclusions This study suggests that adequate management of GOH is crucial for promoting a better QoL and a high degree of cognitive function among seniors. To prevent cognitive impairment, such as dementia, future studies should take a more targeted approach by examining data according to each cognitive domain and various socio-demographic factors.